Comprehensive Review and Analysis of Image Encryption Techniques - K. Mahalakshmi; Sivakumar Nagarajan (IEEE Access, 2025)
The rapid growth of digital media has increased the need to protect image data from unauthorized access, particularly in fields such as medical imaging, military communication, and online content distribution. This paper provides a comprehensive review of advanced image encryption techniques aimed at preserving the confidentiality and integrity of visual information. The analysis includes traditional cryptographic methods, such as AES, RSA, and Blowfish, as well as quantum encryption, chaos-based encryption, DNA encryption, frequency domain techniques, neural network-based methods, and compressive sensing. Each technique was evaluated based on key performance metrics, including the resistance to differential and statistical attacks, computational efficiency, noise resilience, key sensitivity, and encryption speed. Through comparative analysis, this study highlights the strengths, weaknesses, and applicability of these methods in various contexts. The review concludes by discussing the current challenges and suggesting future research directions to improve the security, scalability, and real-time processing capabilities of image encryption systems.